Propagation of bichromatic-bidirectional waves - Silva,Mario Grüne de Souza e (2019)
ABSTRACT This study aims to investigate the transformations experienced by the mean water level and radiation stress tensor during the propagation of Bichromatic-Bidirectional (Bi-Bi) waves on a slope of 1:22 and water depth varying from 55 cm to 26 cm, simulating laboratory conditions. A computer program written in Python was used to compute those quantities at different combinations of wave angles and periods. The setup and setdown of the mean water level are strongly dependent on the combination of periods and direction of the primary waves, as they propagate along the slope, modifying the bound infragravity wave. Mohr’s circles for the radiation stress tensor showed significant changes of diameter and center at different points along the basin. The radiation stress components for the Bi-Bi waves are the sum of the stresses associated with each primary wave and a nonlinear term which results from the interference between primary waves. Disregarding these nonlinear terms may significantly affect the nearshore hydrodynamics prediction.